If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 3n = 6n + 4 Reorder the terms: 1 + 3n = 4 + 6n Solving 1 + 3n = 4 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 1 + 3n + -6n = 4 + 6n + -6n Combine like terms: 3n + -6n = -3n 1 + -3n = 4 + 6n + -6n Combine like terms: 6n + -6n = 0 1 + -3n = 4 + 0 1 + -3n = 4 Add '-1' to each side of the equation. 1 + -1 + -3n = 4 + -1 Combine like terms: 1 + -1 = 0 0 + -3n = 4 + -1 -3n = 4 + -1 Combine like terms: 4 + -1 = 3 -3n = 3 Divide each side by '-3'. n = -1 Simplifying n = -1
| 1/2+3/4z=-5/2 | | 15-12x=2x+13 | | 9x-4=7x-1 | | 9x-4+7x-1= | | E=ex | | k^2+4k+4=-7 | | 5(a-4)=6(a-7) | | -[8x+(3x+8)]=1-(3x+3) | | -0.64-6.7u=-6.7u | | 8-3[5-(4y-8)]=0 | | -13+2r+2-r=1+4r | | x^5+3x^4-3x^3-x^2-3x+3=0 | | 17p-1=3p+12+14p | | 10a-45=3(a-15) | | x+92=-47 | | -4(1-4v)-6=-32+5v | | -2+4z=4z-2 | | 10a-45=3a-45 | | 2r+1=4r-1 | | x-3=-40 | | 8(c-3)=5c+24 | | 79+x=94 | | 3x-4(2x-9)=5x+11 | | w=100/4 | | -19.55-6.6j=-19.3j+17.1j+18.73 | | (-51)+x=38 | | 6x+4x=18 | | 8h-11(h+4)=-77 | | 7x+4x=-x | | 1108473/4=x | | 7(z+11)=4(z+11) | | 3X^2-20x+15=0 |